2017
DOI: 10.1038/ncomms14828
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies six novel risk loci for primary biliary cholangitis

Abstract: Primary biliary cholangitis (PBC) is an autoimmune liver disease with a strong hereditary component. Here, we report a genome-wide association study that included 1,122 PBC cases and 4,036 controls of Han Chinese descent, with subsequent replication in a separate cohort of 907 PBC cases and 2,127 controls. Our results show genome-wide association of 14 PBC risk loci including previously identified 6p21 (HLA-DRA and DPB1), 17q12 (ORMDL3), 3q13.33 (CD80), 2q32.3 (STAT1/STAT4), 3q25.33 (IL12A), 4q24 (NF-κB) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 43 publications
3
78
1
Order By: Relevance
“…Thus, the IL-12 signaling pathway appears to be a key player in the pathogenesis of PBC worldwide. To support this hypothesis, STAT4, which factors prominently in IL-12 signal transduction polymorphisms, was associated with susceptibility in Japanese and Han Chinese PBC patients [38,43].…”
Section: Gwass On Pbcmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, the IL-12 signaling pathway appears to be a key player in the pathogenesis of PBC worldwide. To support this hypothesis, STAT4, which factors prominently in IL-12 signal transduction polymorphisms, was associated with susceptibility in Japanese and Han Chinese PBC patients [38,43].…”
Section: Gwass On Pbcmentioning
confidence: 84%
“…Among the SNPs previously reported to be associated with susceptibility to PBC, only HLA has been consistently linked to the disease in distinct patient cohorts across ethnicities as depicted by many significant dots on genome-wide Manhattan plots of GWASs [34][35][36][37][38][39][40][41][42][43].…”
Section: Associations Between Hla and Pbc Susceptibilitymentioning
confidence: 99%
“…(10)(11) In addition to the high concordance among monozygotic twins compared with dizygotic twins with PBC (5) , the strong association with human leukocyte antigen alleles, which vary by ethnicity, supports a genetic cause of inherited risk. (12)(13)(14)(15)(16)(17)(18)(19)(20) Despite progress, only an estimated 15% of the variability of the disease has been accounted for by genetic studies. (21) Environmental risks have been suggested by several large case-control cohort studies that have found associations with urinary tract infections, reproductive hormone replacement, nail polish, and past cigarette smoking.…”
Section: Preamblementioning
confidence: 99%
“…(2) Several large-scale genome-wide association (GWA) studies in European, Japanese, and Han Chinese PBC cohorts have pointed to a strong genetic predisposition to PBC. (3)(4)(5)(6)(7) Specific human leukocyte antigen (HLA) alleles and common polymorphisms in interleukin 12 (IL12), IL12 receptor (IL12R), tumor necrosis factor superfamily member 15 (TNFSF15), IL21, IL21R, and other immune-associated genes have been implicated in PBC pathogenesis. (3,5,6) Although these studies provided many insights in our understanding of PBC pathogenesis, no further studies have examined the genetics of subphenotypes in PBC.…”
Section: And Xiong Mamentioning
confidence: 99%